Substituted N-phenylpyrazine-2-carboxamides, their synthesis and evaluation as herbicides and abiotic elicitors - Dolezal, Martin; Tůmová, Lenka; Kesetovicová, Diana; Tůma, Jirí; Králová, Katarína (Molecules (Basel, Switzerland), 2007)
The condensation of substituted pyrazine-2-carboxylic acid chlorides with ring-substituted anilines yielded five substituted pyrazine-2-carboxylic acid amides. Thesynthesis, and analytical, lipophilicity and biological data of the newly synthesizedcompounds are presented in this paper. The photosynthesis inhibition, antialgal activityand the effect of a series of pyrazine derivatives as abiotic elicitors on the accumulation offlavonoids in a callus culture of Ononis arvensis (L.) were investigated. The most activeinhibitor of the oxygen evolution rate in spinach chloroplasts was 6-chloro-pyrazine-2-carboxylic acid (3-iodo-4-methylphenyl)-amide (2, IC(50) = 51.0 micromol.L(-1)). The highestreduction of chlorophyll content in Chlorella vulgaris was found for 5-tert-butyl-N-(4-chloro-3-methylphenyl)-pyrazine-2-carboxamide (3, IC(50) = 44.0 micromol.L(-1)). The maximalflavonoid production (about 900%) was reached after a twelve-hour elicitation processwith 6-chloropyrazine-2-carboxylic acid (3-iodo-4-methylphenyl)-amide (2).
Keywords: Flavonoids; acetamidy; chlorofyl; flavonoidy; herbicidy; Chlorella vulgaris; chloroplasty; Chlorophyll; Chloroplasts; Oxygen; Herbicides; kyslík; Acetamides